Limiting Behavior of the Partial Sum for Negatively Superadditive Dependent Random Vectors in Hilbert Space. (24th August 2020) - Ko, Mi-Hwa
Abstract : In this paper, We study the complete convergence and Lp - convergence for the maximum of the partial sum of negatively superadditive dependent random vectors in Hilbert space. The results extend the corresponding ones of Ko (Ko, 2020) to H -valued negatively superadditive dependent random vectors.